Does physical activity affect social skills and antisocial behavior? The gender and only child status differences - Yuke Yang; Yan Gao; Xiangren Yi; Yining Hu; Liangyu Zhao; Lu Chen; Wenze Sui; Shuoqin Zhang; Sen Ma (Frontiers Media S.A., 2024)
BackgroundThis study aims to explore the effects of physical activity on adolescents' social skills and antisocial behavior, as well as gender and only child status differences among Chinese adolescents.MethodsWe used longitudinal data, collecting baseline data for 2021-2022 and follow-up in 2022-2023. A total of 3,206 students were enrolled, including 1,510 males (Age ± SE: 13.62 ± 1.69) and 1,696 females (Age ± SE: 14.09 ± 1.85), 1,339 only children (Age ± SE: 13.76 ± 1.95), and 1,867 non-only children (Age ± SE: 13.95 ± 1.66). The fixed effects model was used to identify the effects of different types of physical activity on adolescent social behavior and the heterogeneity analysis.Results(1) We found that skipping rope (β = 2.284, t = 5.76), walking (β = 3.495, t = 9.53), cycling (β = 1.271, t = 3.21), jogging (β = 2.614, t = 5.92), and badminton (β = 1.409, t = 2.96) had a positive impact on adolescents' social skills. Tag games (β = −1.615, t = −3.83), swimming (β = −2.862, t = −4.42), dancing (β = −1.11, t = −2.29), and skiing (β = −2.771, t = −3.27) had a negative impact on adolescents' social skills. Skipping rope (β = −1.596, t = −5.86), walking (β = −1.814, t = −7.44), cycling (β = −1.066, t = −4.07), and jogging (β = −1.617, t = −5.30) tended to reduce adolescents' antisocial behavior. Tag games (β = 1.685, t = 5.54), swimming (β = 0.947, t = 2.06), ice skating (β = 1.772, t = 2.71), and skiing (β = 1.468, t = 2.31) tended to increase adolescents' antisocial behavior. In addition, we found that these effects differ by gender and only child status. (2) Boys had significantly higher participation rates in activities. Only children had higher participation rates in skipping rope, baseball or softball, and volleyball, but non-only children had higher participation rates in walking, cycling, jogging, other aerobic exercises, and badminton. (3) Girls had higher social skills, but boys and only children had significantly higher rates of antisocial behavior.ConclusionOur results provide a novel understanding that can inform interventions and improvements in social behavior among Chinese adolescents. Stakeholders such as educators, policymakers, and health professionals can develop more tailored and effective strategies to promote positive social development among adolescents.